Uji Efektivitas Aplikasi Cendawan Entomopatogen Metarhizium anisopliae Terhadap Mortalitas Wereng Batang Coklat (Nilaparvata lugens Stal.) - Prisilya, Erika; Afifah, Lutfi; Sugiarto, Sugiarto; Kurniati, Anik (JURNAL AGROPLASMA, 2023)
Nilaparvata lugens is one of the harmful pests that causes the quantity and quality of rice yields to decrease. The use of chemical pesticides to control pests has a negative impact on the environment and farmers. Biological control using the entomopathogenic fungus Metarhizium anisopliae safe to use to treat pest attacks. The purpose of this study was to determine the effectiveness of using the entomopathogenic fungus M. anisopliae on mortality N. lugens. The method used in this study is an experimental method with a single factor Completely Randomized Design (CRD). This study used liquid suspension conidia density of M. anisopliae consisting of 5 treatments and 4 repetitions: A (sterile distilled water) as control; B (density 106 conidia/ml); C (density 107 conidia/ml); D (density 108 conidia/ml); E (density 109 conidia/ml). Each experimental unit was infested with 10 instar 3 N. lugens and observed mortality for 7 days after application (hsa). The highest mortality calculation result for N. lugens was shown by application of M. anisopliae suspension at density 10 9 conidia/ml of 97,50% and probit analysis yielded an LC50 value of 8,78 x 108 conidia/ml which killed 50% N. lugens pests. Biological control using the entomopathogenic fungus M. anisopliae is effective for controlling N.lugens and high conidia density can infect the pest with higher mortality.